Distributed spectrum sensing with multiantenna sensors under calibration errors - Daniel Romero; R. López-Valcarce (IEEE Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2011)
Spectrum sensing design for Cognitive Radio systems is challenged by the nature of the wireless medium, which makes the detection requirements difficult to achieve by standalone sensors. To combat shadowing and fading, distributed strategies are usually proposed. However, most distributed approaches are based on the energy detector, which is not robust to noise uncertainty. This phenomenon can be overcome by multi-antenna sensors exploiting spatial independence of the noise process. We combine both ideas to develop distributed detectors for multiantenna sensors. Fusion rules are provided for sensors based on the Generalized Likelihood Ratio as well as for ad hoc detectors derived from geometric considerations. Simulation results are provided comparing the performance of the different strategies under lognormal shadowing and Ricean fading.
Keywords: ad hoc detectors; antenna arrays; calibration; calibration errors; cognitive radio; energy detector; generalized likelihood ratio; log normal distribution; lognormal shadowing; multiantenna sensors; Ricean fading; spectrum sensing; wireless medium